Poggio Bracciolini and the Re(dis)covery of Antiquity: Textual and Material Traditions Proceedings of the Symposium Held at Bryn Mawr College on April 8-9, 2016 - Ricci, Roberta (Atti, 2020)
This collection draws strength from its cross-disciplinarity, featuring contributions by scholars who investigate Bracciolini's contribution to many fields of knowledge in the Western tradition, spanning across politics and historiography, material and print culture, philology and manuscript studies, calligraphy and palaeography. The essays touch upon intertwined aspects of early Renaissance in its recovery of the classical tradition where the concept of humanitas extends to the manuscript itself. "This distinguished collection of essays adds a wealth of scholarly detail to our understanding of the myriad-minded Renaissance humanist Poggio Bracciolini. And, in doing so, it also managed to capture much of the range and flavour of this extraordinary figure: his learning, his passionate interest in antiquity, his civic pride, and his brilliance in calligraphic design, as well as his ceaseless self-promotion , his enmities, his taste for obscenity, and his penchant for moralizing. Poggio's startling energy and the energy of the whole period course through these pages" (Stephen Greenblatt)